2008
DOI: 10.1098/rspb.2008.0066
|View full text |Cite
|
Sign up to set email alerts
|

MHC-mediated mate choice increases parasite resistance in salmon

Abstract: Natural (parasite-driven) and sexual selection are thought to maintain high polymorphism in the genes of the major histocompatibility complex (MHC), but support for a link between mate choice, MHC variation and increased parasite resistance is circumstantial. We compared MHC diversity and Anisakis loads among anadromous Atlantic salmon (Salmo salar L.) returning to four rivers to spawn, which had originated from natural spawning (parents allowed to mate freely) or artificial crosses (parents deprived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 48 publications
1
112
1
Order By: Relevance
“…Third, paternity is sometimes biased in favour of MHCdissimilar parents (e.g. Atlantic salmon, Salmo salar: Consuegra & de Leaniz 2008;passerines: Freeman-Gallant et al 2003;Richardson et al 2005; grey mouse lemur, Microcebus murinus: Schwensow et al 2008). However, the relative number of sperm inseminated by competing males into a female is a well-known predictor of fertilization success under sperm competition in the fowl (Martin et al 1974), as in several other species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Third, paternity is sometimes biased in favour of MHCdissimilar parents (e.g. Atlantic salmon, Salmo salar: Consuegra & de Leaniz 2008;passerines: Freeman-Gallant et al 2003;Richardson et al 2005; grey mouse lemur, Microcebus murinus: Schwensow et al 2008). However, the relative number of sperm inseminated by competing males into a female is a well-known predictor of fertilization success under sperm competition in the fowl (Martin et al 1974), as in several other species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Atlantic salmon (Landry et al, 2001;Consuegra and de Leaniz, 2008) and Chinook salmon (Neff et al, 2008) revealed that reproductive success was positively correlated with MHC class II allelic distance of mates (disassortative). In these studies, females and males were allowed to spawn freely without interference and it is not possible to differentiate between the impact of female choice and male competitiveness pre-and post-spawning on the reproductive success.…”
Section: The Mhc and Fertilization Successmentioning
confidence: 99%
“…Given the high polymorphism and potential benefits associated with MHC-based mate preference, 2 main hypotheses have been proposed: (1) MHC genotypes could function to discriminate close kin, and might help females to avoid inbreeding (Penn & Potts 1999, Landry et al 2001, or (2) negative assortative mating based on MHC genotype might improve the pathogen resistance of offspring (Doherty & Zinkernagel 1975, Landry et al 2001. Mate selection based on MHC genotype has been demonstrated in several fish species to date, including three-spined sticklebacks Gasterosteus aculeatus (Reusch et al 2001, Aeschlimann et al 2003, Milinski et al 2005), a variety of salmonids (Atlantic salmon Salmo salar: Landry et al 2001, Consuegra & de Leaniz 2008brown trout Salmo trutta: Forsberg et al 2007; Chinook salmon Oncorhynchus tshawytscha: Neff et al 2008, Garner et al 2010, and other freshwater fish species (e.g. rose bitterling Rhodeus occelatus: Casalini et al 2009).…”
Section: Introductionmentioning
confidence: 99%